Non-invasive water status detection in grapevine (Vitis vinifera L.) by thermography - zia, shamaila; Spohrer, Klaus; Merkt, Nikolaus; Wenyong, Du; Xiongkui, He; M, Joachim (International Journal of Agricultural and Biological Engineering, 2010)
Grapevines are preferentially grown under mild to moderate water stress conditions to achieve the best compromise between wine quality and quantity. Water status detection for advanced irrigation scheduling is frequently done by predawn leaf water potential (ΨPD) or leaf stomata conductance (gL) measurements. However, these measurements are time and labor consuming. Therefore, the use of infrared thermography (IRT) opens up the possibility to study large population of leaves and to give an overview on the stomatal variation and their dynamics. In the present study IRT was used to identify water stress of potted grapevines. In order to define the sensitivity of IRT measurements to water stress, the IRT-based water status information were compared with simultaneously measured ΨPD and gL data. Correlations between IRT-based CWSI data on the one hand and gL and ΨPD on the other showed the potential of IRT for water stress detection. However, the CWSI calculation procedure is laborious and the sensitivity of CWSI for water stress detection still needs to be improved. Therefore, further improvements are necessary in order to apply remote IRT-based systems for irrigation scheduling in the field. Keywords: infrared thermography, leaf temperature, stomata conductance, leaf water potential, plant water stress and crop water stress index (CWSI) DOI: 10.3965/j.issn.1934-6344.2009.04.046-054 Citation: Shamaila Zia, Klaus Spohrer, Nikolaus Merkt, Du Wenyong, Xiongkui He, Joachim Müller. Non-invasive water status detection in grapevine (Vitis vinifera L.) by thermography. Int J Agric & Biol Eng, 2009; 2(4): 46<span style="font-size: 9.5pt; line-height: 140%; font-family: